Feeding Relationships of Dominant Fish Species in the Visayan Sea - Mequila, Annie Trixie; Campos, Wilfredo (Science Diliman: A Journal of Pure and Applied Sciences; Vol 19 No 1 (2007), 2007)
This study examines the diet composition of 15 fish species belonging to 11 families in the Visayan Sea. A total of 50 prey items were identified from 323 stomachs examined. Cluster analysis was used to assess similarities in the composition of prey items in individuals of similar sizes but of different species, and in individuals of the same species but of different size categories. The results showed high similarity among individuals of the same species and low similarity between different species of similar size categories. Two major clusters were formed, showing generalist feeding (high niche widths) and trophic segregation (low food niche overlap). These suggest that food resources in the Visayan Sea are not limited and that a wide range of habitats is available to the fish community.